Corpus approach to teaching Czech as a foreign language in university courses - Zasina, Adran Jan (Bohemistyka, 2022)
The corpus approach to teaching Czech as a foreign language has not gained its stable place in academic language teaching practice in spite of growing interest in the last years. A comprehensive framework of corpus-based exercises usage and their influence on students' language development is still missing. This article aims to verify the data-driven learning (DDL) method in teaching Czech at university level. The analysis was based on an experiment in which an experimental group using the corpus approach was examined in comparison with a control group. The research was conducted in the form of a one-semester course for Polish students of Czech studies. The results have proven that thanks to DDL activities, students accomplished positive outcomes and, in several areas, had even better results in comparison with control group. They substantially improved in terms of grammatical gender, vocalisation of prepositions, and genitive singular and plural. For these three language phenomena concrete application of corpus exercises was presented. The study confirmed that the clear and systematic procedure presented in the corpus approach to teaching contributed to the fixation of taught material. Employment of DDL methods in university language courses has a chance to become a permanent means used by teachers and students in language discovery in the future.